2018
DOI: 10.1016/j.pneurobio.2017.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Nano- and neurotoxicology: An emerging discipline

Abstract: The present critical review analyzes the question of how nanoparticles from continuously growing industrial production and use of nanomaterials may impact human brain health. Available evidence suggests incomplete effectiveness of protective barriers of the brain against nanoparticles translocation to the brain. This raises concerns of potential effects of manufactured nanoparticles on brain functions, given that nanoparticle's potential to induce oxidative stress, inflammation, death by apoptosis, or changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
61
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(64 citation statements)
references
References 209 publications
(228 reference statements)
3
61
0
Order By: Relevance
“…That makes them ideal for in vivo imaging and immunofluorescence (Minami et al, 2012;Zhang, 2013). Additionally, QDs were discovered to be quickly transported from the nose to the brain primarily by olfactory uptake and via fast axonal transport (Bencsik, Lestaevel, & Canu, 2017). Thus, it is essential to evaluate the biosafety of CdTe QDs in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…That makes them ideal for in vivo imaging and immunofluorescence (Minami et al, 2012;Zhang, 2013). Additionally, QDs were discovered to be quickly transported from the nose to the brain primarily by olfactory uptake and via fast axonal transport (Bencsik, Lestaevel, & Canu, 2017). Thus, it is essential to evaluate the biosafety of CdTe QDs in the central nervous system (CNS).…”
Section: Introductionmentioning
confidence: 99%
“…Despite a paucity of epidemiological data regarding the health effects of engineered nanomaterials (ENMs) , both human and animal experiments reported that ENMs elicited activation of inflammatory and oxidative stress responses that could be monitored in different biological matrices as preclinical alterations (Bencsik et al 2018;Schulte et al 2019). Such preclinical alterations may function both as indicators of early effects before J o u r n a l P r e -p r o o f clinical manifestations may occur and as indirect markers of exposure, although with a low specificity for ENMs (Schulte et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the choice of appropriate biological matrix for a biomarker validation for non-invasive biological J o u r n a l P r e -p r o o f monitoring in occupational setting has a paramount importance. For ENMs, the respiratory tract is the primary route of exposure in occupational settings, thus the respiratory system plays a central role in the toxicokinetic and toxicodynamic profile of ENMs (Bencsik et al 2018;Schulte et al 2019). ENMs may enter other human organs and generate toxicity after they are absorbed into the bloodstream through the respiratory systems (Mu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence to show that exposure to polluted ambient air is also injurious to the brain (Brockmeyer and D'Angiulli, 2016;Clifford et al, 2016;Power et al, 2016;Babadjouni et al, 2017;Cohen et al, 2017;Sripada, 2017;Underwood, 2017;Bencsik et al, 2018). Among other air pollutants, the fine particulate matters (PM) with an aerodynamic diameter of <2.5 µm (PM2.5), which include ultrafine PM with a size of <200 nm (PM0.2) and nanometersized PM (nPM) or nanoparticles (NPs), has attracted particular attentions for their potential damage to the brain because they more readily enter the brain; they can penetrate the olfactory epithelium and, alternatively and/or additionally, travel deep into the airways and lungs, infiltrate into the blood circulation, and finally cross the blood-brain barrier (BBB) (Heusinkveld et al, 2016;Maher et al, 2016;Underwood, 2017;Bencsik et al, 2018). Such tiny particles in ambient air can be mainly derived from diesel exhaust (DE) and traffic/combustion-related air pollution, and also increasingly result from manufacturing, application, and subsequent release of nanomaterials (Bencsik et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Among other air pollutants, the fine particulate matters (PM) with an aerodynamic diameter of <2.5 µm (PM2.5), which include ultrafine PM with a size of <200 nm (PM0.2) and nanometersized PM (nPM) or nanoparticles (NPs), has attracted particular attentions for their potential damage to the brain because they more readily enter the brain; they can penetrate the olfactory epithelium and, alternatively and/or additionally, travel deep into the airways and lungs, infiltrate into the blood circulation, and finally cross the blood-brain barrier (BBB) (Heusinkveld et al, 2016;Maher et al, 2016;Underwood, 2017;Bencsik et al, 2018). Such tiny particles in ambient air can be mainly derived from diesel exhaust (DE) and traffic/combustion-related air pollution, and also increasingly result from manufacturing, application, and subsequent release of nanomaterials (Bencsik et al, 2018). In general, the smaller their size, the greater their capacity of inducing oxidative stress and thus the more severe the resulting cytotoxicity is (Underwood, 2017).…”
Section: Introductionmentioning
confidence: 99%